أهمية النقل في الامداد - مغربي, محمد (My University, 2020)
important logistics function becomes productive organizational functions and commercial about the material conditions contained supply , production , distribution and flow of information . among the main logistics activities , we find that transport logistics activities , we find that transport logistics is the main driver for businesses and the quality of transport services where it adds value to good or products by providing space time benefit , in the transportation e expense account for much of the total cost of logistics activities. this is what led to the attention of the various transport facilities and work supply strategies and try to find solutions to the pollution problem by transport .
تلخيص فصول تطبيقية متقاربة مع موضوع المذكرة
Keywords: logistics، transport services،quality.